Awareness of Life Insurance Products among Consumers in Kathmandu Valley - Shrestha, Namisha; Rawat, Ramesh (Nepalese Journal of Finance, 2025)
This study examines awareness of life insurance products among consumers in Kathmandu Valley. Intention to purchase life insurance is the dependent variable. The selected independent variables are quality of service, safety and protection from products, financial literacy, role of agent and premium rates. The primary source of data is used to assess the opinions of respondents regarding quality of service, safety and protection from products, f inancial literacy, role of agent and premium rates. The study is based on primary data of 127 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of awareness of life insurance products among consumers in Kathmandu Valley. The study showed a positive impact quality of service on intention to purchase life insurance. It indicates that higher the quality of service, higher would be the intention to purchase life insurance. Similarly, the study showed a positive impact of safety and protection from products on intention to purchase life insurance. It indicates that higher the safety and protection from products, higher would be the intention to purchase life insurance. The study also revealed a positive impact of financial literacy on intention to purchase life insurance. It indicates that f inancial literacy leads to intention to purchase life insurance. Likewise, the study observed a positive impact of role of agent on intention to purchase life insurance. It indicates that role of agent leads to intention to purchase life insurance. Similarly, the study observed a positive impact of premium rates on intention to purchase life insurance. It indicates that premium rates leads to intention to purchase life insurance.